Improved clinical outcomes after non-invasive oocyte selection and Day 3 eSET in ICSI patients - Inge Van Vaerenbergh; Tom Adriaenssens; Wim Coucke; Lisbet Van Landuyt; Greta Verheyen; Michaël De Brucker; Michel Camus; Peter Platteau; Michel De Vos; Elien Van Hecke; André Rosenthal; Johan Smitz (BMC, 2021)
Abstract Background Non-invasive oocyte quality scoring, based on cumulus gene expression analysis, in combination with morphology scoring, can increase the clinical pregnancy (CPR) and live birth rates (LBR) in Day 3 eSET (elective single embryo transfer) ICSI patients. This was first investigated in a pilot study and is now confirmed in a large patient cohort of 633 patients. It was investigated whether CPR, LBR and time-to-pregnancy could be improved by analyzing the gene expression profile of three predictive genes in the cumulus cells, compared to patients with morphology-based embryo selection only. Methods A large interventional, non-randomized, assessor-blinded cohort study with 633 ICSI patients was conducted in a tertiary fertility center. Non-PCOS patients, 22-39 years old, with good ovarian reserve, were stimulated with HP-hMG using a GnRH antagonist protocol and planned for fresh Day 3 eSET. The cumulus cells from individually denuded oocytes were ranked by a lab-developed cumulus cell test: qRT-PCR for three predictive genes (CAMK1D, EFNB2 and SASH1) and two control genes (UBC, B2M). The embryo selected for transfer was highest ranked from the pool of morphologically transferable Day 3 embryos. Patients in the control (n = 520) and experimental arm (n = 113) were compared for clinical pregnancy and live birth, using a weighted generalized linear model, and time-to-pregnancy using Kaplan-Meier curves. Results The CPR was 61% in the experimental arm (n = 113) vs 29% in the control arm (n = 520, p < 0.0001). The LBR in the experimental arm (50%) was significantly higher than in the control arm (27%,p < 0.0001). Time-to-pregnancy was significantly shortened by 3 transfer cycles independent of the number of embryos available on Day 3 (Kaplan-Meier, p < 0.0001). Cumulus cell tested patients < 35 years (n = 65) or ≥ 35 years (n = 48) had a CPR of 62 and 60% respectively (ns). For cumulus cell tested patients with 2, 3-4, or > 4 transferable embryos, the CPR was 66, 52, and 67% (ns) respectively, and thus independent of the number of transferable embryos on Day 3. Conclusions This study provides further evidence of the clinical usefulness of the non-invasive cumulus cell test over time in a larger patient cohort. Trial registration Clinicaltrials.gov, NCT03659786 / NCT02962466 (Registered 6Sep2018/11Nov2016, retrospectively registered.